Urban Wet‐Weather Flows. (1st October 2014) - Sample, David J.; Rangarajan, Srinivasan; Lee, Joong; Manguerra, Henry; Boone, Matthew
Abstract : This literature review summarizes significant technical literature published in 2012 and 2013 in all primary areas of urban wet‐weather flows. The review covers a range of topics including characterization, pollution sources, monitoring and sampling, surface and groundwater impacts, mathematical modeling tools and decision support systems, regulatory policies, and control and treatment technologies. Some gaps in the literature compilation have also been identified and presented to support future research efforts.